Pilot Project Village Head Election with Electronic Voting System (e-voting) in Malinau District, North Kalimantan Province - Eka Lesmana, Bayu; Suherman, Diki (GoResearch - Research & Publishing House, 2023)
In the context of holding simultaneous Pilkades to make it more effective and efficient and to minimize the occurrence of disputes caused by invalid votes, On March 8, 2021, the Ministry of Home Affairs issued Circular Letter Number 141/1115/BPD to regents/mayors throughout Indonesia concerning Implementation of Village Head Elections simultaneously through e-voting. However, the reality is that e-voting-based pilkades are still not massively implemented in Indonesia. The research method used in this writing is the descriptive research method with a qualitative approach. This research method was used because it aims to identify the readiness and success of the Pilkadades pilot project using the electronic voting method based on the general election principle. The results of the discussion of this article are that, in 2023 Malinau district, North Kalimantan Province, will be one of the districts that will hold village head elections through e-voting. the implementation can be categorized as successful, without harming the principles of general elections, success can be seen during the Pilkades implementation with the e-voting system, no fraud was found from any party so the election process ran in an orderly and smooth manner following the System Operational Procedure (SOP) which has been set by the National Research and Innovation Agency (BRIN).